EVALUATION OF THE CARE GIVEN TO DIABETIC SERVICE USERS IN A HEALTH CARE UNIT - Aline Mariana Gafuri; Beatris Mario Martin; Carolina Passos Rocha; Fernanda Rackes da Silva; Roberta Luiza Longo; Guilherme Souza Cavalcanti de Albuquerque (Universidade Federal do Paraná, 2011)
This study aims to evaluate the care programmed for diabetics in a Basic Healthcare Unit of the Brazilian National Health in a county in the metropolitan region of Curitiba, in the state of Paraná. Students and professors of an extension project identified the diabetics registered in the unit and analysed how it controlled the condition. Service users who did not comply with treatment or who did not experience improvements in their condition were visited for identification of the reasons, care orientation and the booking of checkups or exams. After the fourth month the analysis was repeated, showing a significant improvement in compliance and in the control of the patients' diabetes. Based on this, there was a revision of the planning and evaluation of care. The opening of the unit to the university's participation constituted an important learning space and contributed to modifying the assistance given to service users, the main objective of the health services.